Functional and Aesthetic Outcome after Syndactyly Release in Children under 5 Years of Age Presenting to Shaikh Zayed Medical Complex Rahim Yar Khan - Razzaq, Nazakat; Khan, Sajid; Asrar, Musadaq; Zahid, Rosheen; Rehmat, Wardah; Karim, Hammad; Saeed, Rimsha (Biological and Clinical Sciences Research Journal, 2025)
Syndactyly is the most common congenital anomaly of the hand, presenting as webbing or fusion of adjacent fingers. In Pakistan, there is limited local data on the postoperative functional and cosmetic outcomes of syndactyly release procedures in pediatric patients. Objective: To assess the functional and aesthetic outcomes after surgical correction of syndactyly and evaluate caregiver satisfaction with the results. Methods: This observational study was conducted at Shaikh Zayed Medical Complex and DHQ Hospital, Rahim Yar Khan, over three months from 25 February 2025 to 25 May 2025. A total of 80 pediatric patients with simple or complex syndactyly were included. Surgical release was performed using standard zigzag incisions with or without skin grafting. Functional improvement, cosmetic appearance, and caregiver satisfaction were assessed using clinical evaluation and a visual analogue scale (VAS) during a 3-month follow-up. Results: The mean age of patients was 3.5 ± 1.2 years. Simple syndactyly was present in 64% of cases. Postoperative assessment revealed satisfactory functional improvement in over 85% of cases. Aesthetic outcomes were rated as excellent or good by 70% of caregivers. Minor complications, such as superficial wound dehiscence, occurred in 6% of patients. No major surgical or graft-related complications were observed. Conclusion: Syndactyly release surgery is effective in restoring hand function and improving aesthetic outcomes in children. High caregiver satisfaction and low complication rates support the implementation of standardized surgical protocols in tertiary care hospitals across Pakistan.